Feasibility study of a tidal energy site in the Piscataqua River, New Hampshire, using large-eddy simulation - Mustafa Meriç Aksen; Mehrshad Gholami Anjiraki; Jonathan Craig; Jang-Geun Choi; Thomas Lippmann; Martin Wosnik; Ali Khosronejad (Advances in Water Resources, 2026)

Modeling the Influence of Directional Swimming Ability in American Lobster ( Homarus americanus ) Postlarvae on Settlement - Jang‐Geun Choi; Joshua T. Carloni; Benjamin C. Gutzler; Winsor Watson; Steven Jury; Thomas C. Lippmann; Jason S. Goldstein (Fisheries Oceanography, 2026)
We developed a particle tracking model for the transport and dispersion of American lobster ( Homarus americanus ) larvae for the Gulf of Maine (GoM) that considers both passively drifting larval stages and their swimming ability during the postlarval (pre‐settlement) stage. The model takes into account two characteristics of the postlarval stage: directional swimming toward shallower regions and diel fluctuations of their swimming speed. Diffusivity (lateral mixing), based on surface GPS drifter observations, was also considered and used to validate this model. Numerical experiments, using the hydrodynamics predicted by the Gulf of Maine Operational Forecasting System (GoMOFS) model, were conducted to test the potential impact of postlarval swimming ability on successful settlement on suitable habitat (defined as regions shallower than 20 m). The results of this experiment showed that elevated swimming ability (18 cm/s) in postlarvae significantly improves settlement success compared to trials modeling postlarvae with a diminished swimming ability (7 cm/s), or no swimming ability (control) at all. In contrast, diel swimming behavior in postlarvae slightly decreased successful settlement. In addition, ocean drifter observations and numerical simulations consistently revealed that successful settlement decreases the further the initial release point of larvae is from the coast. Combined, these experiments indicate that both the swimming ability of postlarvae and the distance they are from shore when they hatch are critical factors that influence their potential to reach viable settlement locations in the GoM. These data also suggest that if the GoM continues to warm, and females move further offshore to avoid warmer inshore waters, the settlement success of their larvae may be compromised.

Biogeochemical dynamics underlying equilibrium between nitrogen fixation and denitrification and its impact on a coastal marine ecosystem model - Jang-Geun Choi; Thomas C. Lippmann (Ecological Modelling, 2024)

New diagnostic sea surface current fields to trace floating algae in the Yellow Sea - Jang-Geun Choi; Deoksu Kim; Jisun Shin; Seon-Woong Jang; Thomas C. Lippmann; Young-Heon Jo; Jinku Park; Sung-Won Cho (Marine Pollution Bulletin, 2023)

Analytical population dynamics underlying harmful algal blooms triggered by prey avoidance - Jang-Geun Choi; Thomas C. Lippmann; Elizabeth L. Harvey (Ecological Modelling, 2023)

Variability of in situ sediment strength and pore pressure behavior of tidal estuary surface sediments - Greg Lucking; Nina Stark; Thomas Lippmann; Stephen Smyth (Geo-Marine Letters, 2017)

Observations of pockmark flow structure in Belfast Bay, Maine, Part 1: current-induced mixing - Christina L. Fandel; Thomas C. Lippmann; James D. Irish; Laura L. Brothers (Geo-Marine Letters, 2017)

Observations of pockmark flow structure in Belfast Bay, Maine, Part 3: implications for sediment transport - Christina L. Fandel; Thomas C. Lippmann; Diane L. Foster; Laura L. Brothers (Geo-Marine Letters, 2017)

Observations of pockmark flow structure in Belfast Bay, Maine, Part 2: evidence for cavity flow - Christina L. Fandel; Thomas C. Lippmann; Diane L. Foster; Laura L. Brothers (Geo-Marine Letters, 2017)

Feeding of Selenium Alone or in Combination with Glucoraphanin Differentially Affects Intestinal and Hepatic Antioxidant and Phase II Enzymes in Growing Rats - Nicole M. Blum; Kristin Mueller; Doris Lippmann; Cornelia C. Metges; Thomas Linn; Josef Pallauf; Andreas S. Mueller (Biological Trace Element Research, 2013)

On Phase Equilibria and Phase Transformations in β/γ-TiAl Alloys – A Short Review - Svea Mayer; Christian Sailer; Thomas Schmoelzer; Helmut Clemens; Thomas Lippmann; Peter Staron; Volker Güther; Masao Takeyama (BHM Berg- und Hüttenmännische Monatshefte, 2011)